Respuesta :

5.

x = -1

y = 3

Step-by-step explanation:

you'll want to cancel the y numbers

5.

-2x-9y=-25

-4x-9y=-23

multiply the bottom with -1 so that you have

positive or +9y

-2x-9y= -25

-1 times (-4x-9y= -23)

-2x-9y= -25

+4x+9y= +23

this equals

2x = -2

x = -1

put -1 where the x is in -2x-9y= -25 to get y

-2(-1) -9y = -25 =

+2 -9y = -25

-9y = -27

y = 3

6.

8x+ y= -16

-3x+ y= -5

multiply 8x+ y= -16 with +3 AND

multiply -3x+ y= -5 with -8

so you can cancel out the x's

+3 (8x+ y= -16)

-8 times (-3x+ y= -5)

8x+ y= -16

+3x -y= +5

equals

24x+ 3y= -48

-24x +8y= -40

11y = -88

y = -8

Answer: just answering so that super smart person can get brainliest :)

Step-by-step explanation:

ACCESS MORE